A A Corpus Based Approach to the Analysis of Structures in Prepositional Phrase - Ni Wayan Swarniti (Yavana Bhasha : Journal of English Language Education, 2021)
The written text can not be separated from using prepositional phrase, becauseprepositional phrase makes a sentence complete grammatically. In this research, there wasan aim that has to be achieved. Namely: to determine the structures of prepositional phrase.This research was descriptive qualitative-quantitative research. The data sources of thisresearch were taken from phrases that have prepositional phrase in 50 articles of law. In thisresearch, corpus linguistic was used as the method of collecting data. Corpus linguistic usedan application in computer. It was AntConc3.2.4w2011. The results of the analysis werepresented by using formal and informal technique. The structures of prepositional phrasefound were 4 structures. They are prep + det + noun, prep + det + adj + noun, prep + noun, andprep + adj + noun. These structures were found based on some words as triggers in thesoftware of corpus linguistics. Namely: down the, up the, around the, into the, with the, withinthe, through, in spite of, instead of, in the, at the and out of.